Global Trends and Research Evolution in Lean Manufacturing and Operational Excellence: A Bibliometric Analysis - Dimas Akbar Rijaya (Publika Bersama Nusantara, 2025)
Lean manufacturing and operational excellence methodologies have emerged as critical drivers of organizational performance, sustainability, and competitive advantage across diverse industrial sectors globally. This bibliometric study analyzes 119 peer-reviewed articles published between 2020 and 2025, sourced from 34 international journals and conferences across 33 countries, to map research trends, thematic domains, and emerging directions in lean production, Six Sigma, and Industry 4.0 integration. Using quantitative and network visualization approaches, our analysis reveals a sustained annual growth rate of 11.38%, with increasing international collaboration patterns (49.58% of publications) and concentrated research contributions from India (16.8%), the United Kingdom (9.2%), and the United States (7.6%). Seven major research clusters were identified: (1) lean production and operational performance, (2) Industry 4.0 integration and digital transformation, (3) sustainable lean practices and green manufacturing, (4) supply chain and manufacturing excellence, (5) Lean Six Sigma methodology and quality enhancement, (6) healthcare and service sector applications, and (7) theoretical frameworks and competency development. The study demonstrates that lean methodologies have evolved from traditional manufacturing-focused approaches toward integrated frameworks encompassing digital technologies, sustainability imperatives, and cross-sectoral applications. Key findings highlight the pivotal role of top management involvement, adequate resource allocation, and strategic alignment in successful implementation. Future research trajectories suggest greater emphasis on machine learning integration, circular economy principles, lifelong learning frameworks, and context-specific adaptations for developing economies. These insights provide scholars, practitioners, and policymakers with an evidence-based foundation for advancing lean thinking in support of global sustainability and digital transformation objectives.